Reflections on the first Grounded Theory Seminar - Tom Andrews (Grounded Theory Review: An International Journal)
I first met Dr. Barney Glaser in April 2002 in Paris, France the evening before the first CGT seminar. At that preliminary gathering I met Dr. Barry Gibson for the first time, who knew Barney. Amongst the PhD students I met was Vivian Martin and Anna Sandgren and we are still in contact. Given the high cost of hotels in Paris, I had to stay some distance from where the seminar was being held. I underestimated the time of getting to the Holiday Inn (the venue) and missed the beginning of the seminar. As a result, I missed Barney’s introduction and was unaware of the format of the seminar. He did not do then what he did in future seminars and that is what he refers to as atmosphering, which sets the stage for conceptual discovery by creating a safe environment for participants to learn and have their issues dealt with in a non-threatening way (Gynnild 2011).